2022
DOI: 10.1007/s40618-022-01955-8
|View full text |Cite
|
Sign up to set email alerts
|

Graves’ orbitopathy post-SARS-CoV-2 vaccines: report on six patients

Abstract: Context Autoimmune and inflammatory thyroid diseases (Graves’ disease, subacute thyroiditis, chronic autoimmune thyroiditis) have been reported following SARS-CoV-2 vaccines but Graves’ orbitopathy (GO) post-COVID-19 vaccination is uncommon. Methods We describe six new patients seen in Endocrinology Departments with Outpatient Clinics for GO following SARS-CoV-2 vaccines in France. Results After COVID-19 vaccination, GO was observed in six pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…where the T lymphocytes are excessively sensitized to the TSH receptor thereby causing GD or TED. 20 It is also possible that epigenetic changes or alterations in the patient's microbiome, such as those demonstrated following mRNA SARS-CoV-2 vaccination, may play a role in TED pathogenesis. 19 Lastly, Sriwijitalai and Wiwanitkit suggested that vaccination-induced increase in blood viscosity is another possible pathophysiological process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…where the T lymphocytes are excessively sensitized to the TSH receptor thereby causing GD or TED. 20 It is also possible that epigenetic changes or alterations in the patient's microbiome, such as those demonstrated following mRNA SARS-CoV-2 vaccination, may play a role in TED pathogenesis. 19 Lastly, Sriwijitalai and Wiwanitkit suggested that vaccination-induced increase in blood viscosity is another possible pathophysiological process.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been 16 cases of reactivation or newonset TED after SARS-CoV-2 vaccination reported. 10,[15][16][17][18][19][20] A summary table (Table 1) is presented comparing the patient characteristics, clinical presentation and treatments of other similar post-vaccination TED patients together with the index patient of this report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…patients (mean age of 53 years) with GO following vaccination [16]. All of these had a previous history of immune thyroid disease.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Four patients had elevated TSH-R-Ab levels. Treatment varied based on the severity and activity of GO, including selenium, intravenous glucocorticoids, teprotumumab, tocilizumab, and orbital decompression, resulting in significant improvement in GO signs and symptoms [16].…”
Section: Accepted Manuscriptmentioning
confidence: 99%